Optimizing discrete V obstacle parameters using a novel Entropy-VIKOR approach in a solar air flow channel. (June 2017) - Sharma, Ashutosh; Chauhan, Ranchan; Singh, Tej; Kumar, Anil; Kumar, Raj; Kumar, Anil; Sethi, Muneesh
Abstract: In this paper the experimental investigation and optimization of the performance of discrete V obstacles in solar air channel is reported. The discrete V obstacles have desperate trend on thermal boundary layer formation on the downside of heat conveying surface. Besides this, increase in friction losses deteriorates the overall performance of the air flow solar channel. Therefore, it becomes essential to optimize the performance defining criteria with their simultaneous consideration and evaluate an optimal parameter set that delivers higher thermal as well as collector efficiency and lower hydraulic performance at the same time. Hybrid Entropy-VIKOR method, a multi criteria decision making approach is therefore applied to the experimental data obtained, which quantifies these criteria as a mutual agreement. Based upon the Entropy-VIKOR optimization methodology, it has been observed that the relative angle of attack, discrete distance ratio and the discrete width ratio of the inserted V obstacle with gaps having numerical value of 0.666, 0.67 and 1.0 presents an optimal parameter set. The enhancement in thermal, hydraulic and collector efficiency yielded at an optimal parameter set is 4.2–6.2, 5.9–8.4 and 1.23–1.47 times respectively with discrete V obstacles compared to air flow channel without obstacles. Highlights: Hybrid Entropy-VIKOR approach is implemented in SAC. N u d V o and f d V o are evaluated based upon which the PDC's are determined. The optimal parameters are: α / 90 = 0.666, W d / l o = 1.0, D d / l o = 0.67 . Enhancement in N u d V o, f d V o and η e f f of 4.2–6.2, 5.9–8.4 and 1.23–1.47 times is achieved. The Entropy-VIKOR is a powerful tool for parametric optimization in SAC.